Molecularly Imprinted Polymers Based Electrochemical Sensor for 2,4-Dichlorophenol Determination - Liu, Benzhi (Polymers (Basel), 2016)
A molecularly imprinted polymers based electrochemical sensor was fabricated by electropolymerizing pyrrole on a Fe(3)O(4) nanoparticle modified glassy carbon electrode. The sensor showed highly catalytic ability for the oxidation of 2,4-dichlorophenol (2,4-DCP). Square wave voltammetry was used for the determination of 2,4-DCP. The oxidation peak currents were proportional to the concentrations of 2,4-DCP in the range of 0.04 to 2.0 µM, with a detection limit of 0.01 µM. The proposed sensor was successfully applied for the determination of 2,4-DCP in water samples giving satisfactory recoveries.